Desconexión moral y disposición psicosocial frente al conflicto armado en jóvenes residentes de la ciudad de Barranquilla (2019)
The objective of this research was to correlate the Mechanisms of Moral Disengagement proposed by Bandura (1990) and the Psychosocial Disposition against Armed Conflict proposed by Alzate, Duran and Sabucedo (2009). The study was carried out with 170 young people from Barranquilla, Colombia. Regarding the measurement of the variables, we used the Spanish version of the Moral Disengagement questionnaire (Rubio-Garay, Amor y Carrasco, 2007) and the Psychosocial Disposition against Armed Conflict questionnaire (Alzate, Duran and Sabucedo, 2009). It was evidenced that there is a low tendency to use the Mechanisms of Moral Disengagement; however, it is worth mentioning that the most used mechanism by young people is the Dissemination of Responsibility. Regarding to the Psychosocial Disposition against Armed Conflict, it was found that there is little preference in the participants for negotiation and social reconciliation. Likewise, from the correlation it has been found that there is a relationship between the mechanisms of Moral Disengagement and some dimensions from the Psychosocial Disposition against Armed Conflict. The most significant findings were related to Moral Justification and Social Reconciliation.